JARIMAH PEMERKOSAAN DALAM QANUN JINAYAT ACEH PERSPEKTIF FEMINIST LEGAL THEORY - Weini Wahyuni (Jurnal Hukum, 2022)
The Qanun Jinayat (Islamic criminal code bylaw) in Aceh has often received criticism from various groups, especially those working on the issue of protecting women and children against sexual violence, including rape, for often harming women rather than accommodating their interests. Article 52 paragraph (1) becomes a stumbling block for female victims of rape to report the crime they experienced because it requires the victim to prepare sufficient preliminary evidence. This is considered a form of discrimination against female rape victims because it multiplies their burden. Using feminist legal theory, this study investigated the structure of injustice that underpins discrimination against women in the construction of legal norms for rape (articles 48-56) of Qanun Jinayat Aceh. A philosophical approach is used in the research to examine in depth the legal norms of rape in the Qanun a quo, especially in the axiological aspect. This study found a link between aspects of masculinity and understanding of religion that supports the structure of injustice in the Qanun Jinayat Aceh which has implications for the emergence of difficulties faced by female victims of rape to access justice. The difficulties faced by female rape victims reflect efforts to perpetuate masculine domination with an interest in making women always languish in the prison of injustice. Due to the lack of efforts to fight for women's access to justice, the construction of legal norms for rape crimes even more echoes the critical legal feminist assumption regarding law as a means of subjugation to women. Instead of empowering, the Qanun a quo further perpetuates female subordination and rape.Â Qanun Jinayat Aceh acapkali mendapat kritik dari berbagai kalangan, khususnya yang bergiat dengan isu perlindungan perempuan dan anak berkaitan dengan jarimah pemerkosaan yang kerap merugikan perempuan ketimbang mengakomodir kepentingan mereka. Pasal 52 ayat (1) menjelma tebing yang tinggi bagi perempuan korban pemerkosaan untuk melaporkan kejahatan pemerkosaan yang dialaminya karena mewajibkan kepada korban untuk menyiapkan bukti permulaan yang cukup. Hal demikian merupakan wujud diskriminasi terhadap perempuan korban pemerkosaan karena melipatgandakan beban mereka, menggunakan feminist legal theory penelitian ini akan menelaah struktur ketidakadilan yang menopang diskriminasi terhadap perempuan dalam konstruksi norma hukum Jarimah Pemerkosaan (pasal 48-56) Qanun Jinayat Aceh. Pendekatan filosofis digunakan dalam penelitian untuk menelaah secara mendalam norma hukum Jarimah Pemerkosaan dalam Qanun a quo, khususnya pada aspek aksiologis, penelitian ini menemukan kait kelindan aspek maskulinitas dan pemahaman terhadap agama yang menopang struktur ketidakadilan dalam Qanun Jinayat Aceh yang berimplikasi pada kemunculan segenap kesulitan yang dihadapi perempuan korban pemerkosaan untuk mengakses keadilan. Kesulitan yang dihadapi perempuan korban pemerkosaan mencerminkan upaya untuk melanggengkan dominasi maskulin yang berkepentingan untuk membuat perempuan senantiasa mendekam dalam penjara ketidakadilan. Lewat minimnya upaya untuk memperjuangkan akses bagi perempuan atas keadilan, konstruksi norma hukum jarimah pemerkosaan justru semakin menggemakan asumsi feminis hukum kritis perihal hukum sebagai alat penundukan terhadap perempuan. Alih-alih memberdayakan, Qanun a quo justru semakin mensubmisi perempuan dan melanggengkan pemerkosaan.